1989
DOI: 10.1139/tcsme-1989-0010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Results on the Tensile Strength of Atmospheric Ice

Abstract: The tensile strength of atmospheric ice samples (glaze and rime) obtained in an open type wind tunnel has been measured. Ice was grown from supercooled water droplets impinging on a rotating aluminium cylinder. In a first series of tests, the liquid water content of air was set at 0,8 g/m3 and the tensile strength of atmospheric ice was measured as a function of temperature ranging from −3 to −20°C, wind velocity during accretion ranging from 10 to 23 m/s and nominal strain rate ranging from 8, 70 × 10-7 to 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The tensile ice adhesion of PP and PE were independent of temperature within the range tested (Fig. 13a), similar to prior studies of tensile ice adhesion on other materials [13,14].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The tensile ice adhesion of PP and PE were independent of temperature within the range tested (Fig. 13a), similar to prior studies of tensile ice adhesion on other materials [13,14].…”
Section: Resultssupporting
confidence: 88%
“…Cut and drill the aluminum sheets ( 9), (13), and ( 26) with respect to the dimensions depicted in Fig. 3.…”
Section: Structural Instructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we refer to ice strength as a bulk property equaling the maximum stress intact ice can sustain before fractures appear at macroscale, and we focus specifically on the tensile stress regime. Although there are some constraints on the tensile strength of glacier ice from laboratory experiments (Currier and Schulson, 1982; Lee and Schulson, 1988; Xian and others, 1989; Druez and others, 1989) and field observations (Vaughan, 1993), the ranges derived from the different methods barely overlap. Further, models disagree about what part of the observed range is relevant to glacier modeling and even what style of deformation – viscous, elastic or a combination – determines the stresses associated with fracture (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in constraining the strength of glacier ice is that estimates derived from laboratory experiments do not agree with the limited estimates from in situ observations. Laboratory estimates range from 0.7 to 3.1 MPa (review by Petrovic, 2003) for laboratory and lake ice; Druez and others (1989) found tensile strength as high as 5 MPa for laboratory-grown glaze ice. In situ observations of glaciers, meanwhile, suggest a tensile strength ranging from 0.09 to 0.32 MPa for glacier ice (Vaughan, 1993).…”
Section: Introductionmentioning
confidence: 99%